An integrated treatment approach in patient with metastatic colorectal cancer and concomitant late cardiovascular complications of chemoradiotherapy for Hodgkin’s lymphoma. Clinical case - Yu. E. Ryabukhina; P. A. Zeynalova; A. A. Akhobekov; D. A. Chekini; E. K. Ibragimov; Z. M. Cheishvili; T. I. Kopaliani; V. E. Gruzdev; A. G. Zhukov; T. T. Valiev (Онкогематология)
The high efficacy of the currently used combined chemoradiotherapy for Hodgkin’s lymphoma not only significantly increased overall survival, but also made it possible for most patients to achieve the same quality of life as in a healthy population. at the same time, the problem of identifying late treatment complications, in particular cardiovascular the high efficacy of the currently used combined chemoradiotherapy for Hodgkin’s lymphoma not only significantly increased overall survival, but also made it possible for most patients to achieve the same quality of life as in a healthy population. at the same time, the problem of identifying late treatment complications, in particular cardiovascular diseases, remains an urgent problem, the timely diagnosis of which is an important task. the development of a second malignant neoplasm and the appointment of drug antitumor therapy with cardiotoxic agents necessitate a multidisciplinary approach. In the presented clinical observation, such tactics of patient management made it possible not only to timely identify late cardiovascular complications of Hodgkin’s lymphoma chemoradiotherapy, but also to conduct treatment for the second malignant disease with cardiotoxic agents with a positive antitumor effect.